Differential Uptake of NAGLU-IGF2 and Unmodified NAGLU in Cellular Models of Sanfilippo Syndrome Type B - Prill, Heather (Mol Ther Methods Clin Dev, 2019)
Sanfilippo syndrome type B, or mucopolysaccharidosis IIIB (MPS IIIB), is a rare autosomal recessive lysosomal storage disease caused by a deficiency of α-N-acetylglucosaminidase (NAGLU). Deficiency in NAGLU disrupts the lysosomal turnover of heparan sulfate (HS), which results in the abnormal accumulation of partially degraded HS in cells and tissues. BMN 250 (NAGLU-insulin-like growth factor 2 [IGF2]) is a recombinant fusion protein developed as an investigational enzyme replacement therapy for MPS IIIB. The IGF2 peptide on BMN 250 promotes enhanced targeting of the enzyme to lysosomes through its interaction with the mannose 6-phosphate receptor. The focus of these studies was to further characterize the ability of NAGLU-IGF2 to clear accumulated HS compared to unmodified NAGLU in primary cellular models of MPS IIIB. Here, we establish distinct primary cell models of MPS IIIB with HS accumulation. These cellular models revealed distinct NAGLU uptake characteristics that depend on the duration of exposure. We found that with sustained exposure, NAGLU uptake and HS clearance occurred independent of known lysosomal targeting signals. In contrast, under conditions of limited exposure duration, NAGLU-IGF2 was taken up more rapidly than the unmodified NAGLU into MPS IIIB primary fibroblasts, astrocytes, and cortical neurons, where it efficiently degraded accumulated HS. These studies illustrate the importance of using physiologically relevant conditions in the evaluation of enzyme replacement therapies in cellular models.